Insights into heterogeneous catalytic activation of peroxymonosulfate by natural chalcopyrite: pH-dependent radical generation, degradation pathway and mechanism - Jiali Peng; Hongyu Zhou; Liu, Wen; Zhimin Ao; Ji, Haodong; Yang Liu; Shijun Su; Gang Yao; Bo Lai (Chemical Engineering Journal, 2020)
In this study, natural chalcopyrite (NCP) was employed in the activation of peroxymonosulfate (PMS) for bisphenol S (BPS) degradation. Firstly, the NCP catalyst was characterized via X-ray diffraction (XRD), scanning electron microscopy and energy dispersive spectroscopy (SEM-EDS) techniques. Then, several key parameters such as catalyst dosage, PMS dosage and initial pH were investigated in NCP/PMS system. Furthermore, the transformation of various free radicals (SO4•−, •OH and O2•−) with the changes of initial pH were investigated by quenching experiments and electron spin resonance (ESR) study. Also, sulfur species cycling of copper and iron species were investigated via exogenous Cu2+ and Fe3+ addition experiments and X-ray photoelectron spectroscopy (XPS) analysis, the result indicated that sulfur species promoted Fe3+/Fe2+ and Cu2+/Cu+ cycles on the NCP surface. Furthermore, thirteen major degradation intermediates of BPS were detected by UPLC-QTOF-MS/MS and density functional theory (DFT) method was used to illustrate possible reaction pathways of BPS. Finally, a reasonable reaction mechanism of NCP/PMS system for BPS degradation was proposed on the basis of the comprehensive analysis. In brief, this work helps to provide useful information for the application of natural metallic sulfide minerals in treatment of contaminated waters.
Keywords: Bisphenol S; DFT calculation; mechanism; Natural chalcopyrite; Peroxymonosulfate